Association between dietary inflammatory index and kidney function in elderly population: Results from a cross-sectional study. Issue 3 (13th May 2019) - Tajik, Somaye; Eimeri, Saragol; Mansouri, Sara; Rahimi-Foroushani, Abbas; Shab-Bidar, Sakineh
Abstract : Purpose: This study aims to investigate the association of the dietary inflammatory index (DII), kidney function and high-sensitivity C-reactive protein (hs-CRP) among the senior population (60-83 years). Design/methodology/approach: This cross-sectional study was conducted in 221 elderly subjects who are living in Tehran, Iran. The DII was calculated from validated semi-quantified food frequency questionnaire, combining putatively pro-inflammatory and anti-inflammatory effects of nutrients, vitamins and trace elements. Biochemical measurements of blood and urine samples were measured. The estimated glomerular ﬁltration rate (eGFR) was assessed from serum creatinine. Findings: A total of 221 subjects with mean BMI of 29.75 and age ranged 60-83 years old were included in the current study. Multiple linear regression analysis showed that eGFR ( ß = –0.471; p = 0.48; 95 per cent CI: –2.90, 2.63), albumin/creatinine ratio (ACR) ( ß = 0.041 p = 0.55; 95 per cent CI: –5.12, 9.46) and hs-CRP ( ß = 0.004; p = 0.55; 95 per cent CI: –0.96, 1.79) were not associated with the DII before and after adjusting for potential confounders, including energy intake, age, sex, BMI, smoking status, physical activity, hypertension, diabetes, use of lipid-lowering medication, angiotensin II receptor blockers (ARB) and angiotensin-converting enzyme inhibitor (ACEI), steroidal and non- steroidal anti-inflammatory medications. Research limitations/implications: Due to the cross-sectional nature of this study, it is difficult to find the cause-and-effect relationship between the DII and the serum hs-CRP concentration. Another limitation of our study is concerning a possible overestimation or underestimation of dietary intakes, because the participants in the study were elderly and FFQ is a memory-based questionnaire. Originality/value: Our findings suggest that the DII score is not associated with serum hs-CRP and kidney function markers in elderly people.